Empowerment of family caregiver in front of stroke in hospital environment - Adriana Bitencourt Magagnin; Ivonete Teresinha Schulter Buss Heidemann (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to understand how the empowerment of family caregivers of people with stroke occurs in the hospital environment. Methods: a qualitative research, participatory action research, articulated with Paulo Freire's Research Itinerary, developed in April 2018 with family caregivers, in a Stroke Unit. Results: three predominant codes were coded: the need for empowerment and autonomy to experience the care situation; the challenges experienced in becoming a caregiver; and family support. Participants presented a lack of information inherent to the care process, with distancing from empowerment to perform the function in dehospitalization. Dialogue revealed empowerment as a possibility for critical awareness and skill development. Conclusions: it highlights the importance of directing health promotion for caregivers, inserting them in the care process, recognizing their needs and intensifying practices that promote empowerment for care, bypassing curative actions.